Effectiveness of a community based programme of physiotherapy on stability, balance and function of stroke patients - T. Puckree; P. Uthum (AOSIS, 2014)
This study assessed the effectiveness of a community based programme of phystiotherapy on stability, baland and function in stroke patients.